Thermal and Compositional Analysis of Orange Essential Oil Obtained from Citrus Industry Waste - Gabriel Ferreira; Louise Sobral; Daniel W. Barreto; Verônica Calado (Journal of Advanced Thermal Science Research, 2020)
During the production of orange juice, more specifically after the commercial extraction of fruit juice, other waste materials are generated, consisting of peel, pieces of membranes, pulp bagasse, juice vesicles and seeds. In this way, the final destination of the waste can become a problem when not managed correctly. Therefore, there are several possibilities for using these solid residues, as they present substances of great commercial interest. In this perspective, the present work evaluates the recovery of orange essential oil from the citrus industry waste using hydrodistillation. The oil obtained was characterized by acidic index, FTIR, GC / MS, TGA and DSC. The results exhibited that oil isolated by hydrodistillation has a similarity with cold-pressed orange oil. The chemical constitution of oil obtained from waste was almost the same as the commercial orange oil analyzed. However, the thermal behaviour presents a few differences in thermal stability and vaporization temperature between analysed essential oils. Therefore, this work produces an alternative to obtain a product with quality, high yields and added value that can be used in cosmetic and pharmaceutical industries.